The differential substitution of dental fricatives : an anatomical perspective - Lin, Jingmin (2019)
The problem of dental fricative substitution remains unresolved, despite the many different theories proposed and approaches taken over the years. This study opts to look at the problem from an anatomical perspective, taking an exploratory and empirical approach in investigating whether or not anatomical variation may play a frequently overlooked role in the production of dental fricatives. The raw linguistic and anatomical data used in this study are from the ArtiVarK subproject, specially designed to examine the relationship between anatomical variation and speech production. Linguistic data was preprocessed in Praat, from which patterns of dental fricative productions across various L2 English speakers were identified, and logistic regression was employed to test the relationship between the anatomical variables and the general success in producing a dental fricative. Preliminary results support a general conclusion that the anterior dentition and anterior oral morphology may indeed impact the successful productions of voiceless dental fricatives, although future confirmatory studies are required to validate the results here. These findings underscore the importance of taking anatomical variation into consideration when examining linguistic phenomena.